2022
DOI: 10.21203/rs.3.rs-1757372/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical sequencing identifies potential actionable alterations in a high rate of urachal and primary bladder adenocarcinomas

Abstract: Administration of targeted therapies provides a promising treatment strategy for rare cancers such as urachal adenocarcinoma (UrC) or primary bladder adenocarcinoma (PBAC), however, the selection of appropriate drugs remains difficult. Therefore, in the present study, we aimed to establish a routine compatible methodological pipeline for the identification of the most important therapeutic targets and potentially effective drugs for UrC and PBAC. Next-generation sequencing using a 161 cancer driver gene panel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Lee et al (2017) reported EGFR amplification in 23.5% of patients (4/17) by detecting somatic copy number aberrations. More recently, Varadi et al (2023) described EGFR mutations in 9.1% (3/33) of UrC cases by applying next-generation sequencing. These authors detected two samples with amplification and one sample with a missense mutation.…”
Section: Targeted Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al (2017) reported EGFR amplification in 23.5% of patients (4/17) by detecting somatic copy number aberrations. More recently, Varadi et al (2023) described EGFR mutations in 9.1% (3/33) of UrC cases by applying next-generation sequencing. These authors detected two samples with amplification and one sample with a missense mutation.…”
Section: Targeted Therapymentioning
confidence: 99%
“…MET can act as a driver of malignant progression but also as a mediator of drug resistance in various cancers. Varadi et al (2023) used a next-generation sequencing approach and identified MET mutations in 12% (4/3) of UrC cases. In addition, these authors detected two samples with functional mutations; one of these was a dysfunctional mutation while the status of the other mutation remained unknown.…”
Section: Mutations Of the Tp53 Pten And Met Genesmentioning
confidence: 99%